Thankful employees: The manifestation of gratitude at work during a pandemic in South Africa - Sekaja, Lusanda; Tully, Courtney A.; Mahlangu, Senzile; de Freitas, Katya; Tyelbooi, Lihle N.; Mjojeli, Bonisiwe P. L.; Mokhethi, Masase E.; Mabitsela, Tshegofatso (Frontiers in Psychology, 2022)
Gratitude or the appreciation of being given something of value, is an important element in positive emotions within positive psychology. Gratitude has been linked to wellbeing and gratitude in the workplace is positively associated with constructs such as performance, organizational citizenship behavior. The pandemic brought on many negative experiences but employees could still find things to be grateful for during this time. The purpose of the study was to understand what aspects of work and the organization employees were grateful for during the pandemic. A generic qualitative approach was used. Participants were sourced from various industries in South Africa using purposive sampling. Data were gathered through 21 semi-structured interviews of working people in South Africa. Braun and Clarke’s thematic analysis revealed five themes, namely, (1) gratitude for no negative work-life changes; (2) gratitude for a caring workplace; (3) gratitude for a new way of working; (4) gratitude for the ability to put oneself first; and (5) gratitude for having resilience, optimism and spirituality as a psychological buffer. Managers should deliberately engage in behaviors that will bring about gratitude from their employees. Employees should reflect on the positive things at work that they are thankful for as a way of enhancing gratitude and thereby, wellness, performance, and commitment. The study combines existing knowledge on gratitude during the pandemic with gratitude in the workplace.